Peer Counseling based on Experiential Learning in Higher Education: A Research & Development Study - Nurul Rahmi; Ermalianti; Heldawati (Bisma The Journal of Counseling, 2023)
Peer counseling can serve as a promising approach to tackle the challenges faced by college students during the critical transition from late adolescence to young adulthood. This form of counseling offers a safe space for them to openly share and discuss their issues. However, research focusing on readily applicable peer counseling materials tailored for the college context remains limited. This study endeavors to bridge this gap. Adopting a research and development design, this article aims to develop a peer counseling module grounded in experiential learning, specifically designed for two faculties in university. The potential users of the module include two counselors and twelve counselees from each respective faculty. The development process follows the Borg & Gall framework, incorporating data collection methods such as focused group discussions, expert validation checklists, and observations. The research findings indicate that the module has been well-received by three experts, who found it to be suitable and relevant, offering constructive feedback for further improvement. During the field test, the developed module proved to be instrumental in assisting counselors in comprehending the implementation stages of peer counseling grounded in experiential learning. Theoretical and practical implications of this research are discussed in-depth, shedding light on the potential impact and relevance of integrating experiential learning into peer counseling practices in higher education.